A REVIEW OF COMPUTER AIDED DIAGNOSTIC SYSTEM FOR BRAIN TUMOUR DETECTION USING K-MEANS CLUSTERING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2016)
The brain is the most important part of the central nervous system. The structure and function of the brain need to be studied non-invasively by researchers and medical practitioners using MRI imaging techniques. The body is formed by number of different types of cells. Each type of cell has special functions. When cells lose the ability to control their growth, they divide too often and without following any law. The extra cells form a mass of tissue called a tumour. MRI acts as an assistant diagnostic tool for the medical practitioners during disease diagnosis and treatment. This imaging modality produces images of soft tissues using MRI technique. The acquired medical images show the internal structure, but the medical practioners want to know more than peer images, such as emphasizing the abnormal tissue, quantifying its size, depicting its shape, and soon.